ASSESSMENT OF THE POLLUTANTS OF POLYCHLORINATED BIPHENYL (PCBs) IN THE COASTAL ENVIRONMENT OF NORTHEAST AREA AND RED RIVER DELTA, VIETNAM - Nghị, Dương Thanh; Thạnh, Trần Đức (Vietnam Journal of Marine Science and Technology, 2014)
The persistence organic pollutants of PCB group (28, 52, 101, 138, 153, 180) were determined in three coastal environment components including water, sediments and tissues of Clam (Meretrix lyrata) in the Northeast area and Red River delta. The samples were collected in March and August, 2012. The results showed that the PCBs were appearing in all water, sediments and tissues of Clam with the concentrations  719.46 - 792.11 ng/L; 9.83 - 14.97 ng/g; 39.79 - 40.30 ng/g  respectively, and  lower than environmental standards. The distribution of total PCBs in the three environmental components were varied by the seasons and space. They were an inversive relationship of  PCBs in the coastal water- sediment environment and tissues of Clam in Northeast area, meanwhile ambient  relationship in  Red River delta.  The bioaccumulation factor (BAF) of the total PCBs  for Clam tissue was in the range from 7.46 to 56.42, higher in  Red River delta, and lower in Northeast area in both rainy and dry seasons.